A review of energy extraction from wind and ocean: Technologies, merits, efficiencies, and cost. (1st January 2023) - Rehman, Shafiqur; Alhems, Luai M.; Alam, Md. Mahbub; Wang, Longjun; Toor, Zakria
Abstract: Sustainable power sources have become indispensable in modern society. The most promising renewable sources of energy are wind and ocean, which are widely distributed worldwide. As such, wind and ocean power technologies have attracted great attention of researchers and engineers, achieving the advanced stage of power development. This work aims to review the possible wind and ocean power technologies, to make a comparative assessment in terms of energy availability, efficiency and cost, and finally to share the acceptance and challenges in the wind and ocean power development. We focus on energy harvesting techniques of onshore and offshore (both fixed and floating foundations) wind energy as well as ocean energy including ocean thermal energy, wave energy, tidal energy, salinity gradient energy, and bioinspired energy harvesting. Given that the theoretical efficiency of a wind turbine is 59.3% maximum (Betz limit), most wind turbines can produce power with 30%–35% efficiency, which suggests a scope of further efficiency improvement. The overall offshore installation costs are 2.5–3.0 times the onshore costs. The vertical and horizontal axis stream turbines extracting tidal energy have a maximum of 35% efficiency while the shrouded horizontal axis stream turbines may reach 42% efficiency. Galloping turbines with triangular and trapezoidal prisms may have an efficiency up to 40% and 45%, respectively. Ocean wave energy can provide a continuous power supply. The technology however requires further improvement to be of commercial use. The bioinspired energy harvesting techniques are in the infant stages while research work on ocean wave energy and offshore wind power is going on a faster pace compared to other technologies. Recently, flow-induced vibration techniques are getting more attention from the scientific community and developing rapidly. Highlights: The latest technological maturity and economical status of wind and ocean driven power generation are reviewed. The development stage, challenges, advantages and disadvantages power generation technologies are discussed. The salient features of energy extraction technologies are highlighted.